REFLECTION OF MORAL ATTITUDES IN MIKHAIL YURIYEVICH LERMONTOV’S WORK “THE HERO OF OUR TIME” (International Congress on Economics, Management and Business Studies, 2026)
This article psychologically analyzes the relationship of Grigory Aleksandrovich Pechorin, the main character of Mikhail Lermontov’s novel “Hero of Our Time” with women, and reveals the conflicts between the concepts of “love” and “play” in Pechorin’s character through the characters of Bella, Marie and Vera.
Keywords: Pechorin, love, game, moral attitude, female image, inner experiences.